Morfotektonik pada Gunung Parang Melalui Pendekatan Geomorfologi Tektonik Digital, Daerah Karangsambung - Ghufrani, Poppy; Soesilo, Joko (OPHIOLITE: Jurnal Geologi Terapan, 2024)
Mount Parang is a sill intrusion formed as partial melting due to tectonic activity namely subduction in Miocene which then broke through the Karangsambung formation and revealed to the surface as Mount Parang. Apart from the Mount Parang intrusion, the result of tectonic activity at that time is hills morphology with landforms in the form of anticline and syncline fold structures that stretch from east to west of the Karangsambung area. The geomorphological approach aims to determine the level of tectonic activity based on morphotectonic analysis around the Mount Parang intrusion. Morphotectonic analysis is conducted through a quantitative approach, by measuring and calculating geomorphic index variables using mathematical formulas. The index variables analysed include hypsometric integral (Hi), basin watershed asymmetry (AF), stream gradient-length index (SL), ratio of valley floor width to valley height (Vf), and mountain front sinuosity (Smf). Based on calculation Hi has a value of 1.0 with SL covering three classes. The AF index has a value of >50 with Vf values is between 0.26 and 0.87 and Smf values between 1.3 and 2.7. Based on these values, it indicates that the area around the Mount Parang intrusion has high tectonic activity.